Evolutionary characterization and pathogenicity of the highly virulent human-porcine reassortant G9P[23] porcine rotavirus HB05 strain in several Chinese provinces - Li, Xi; Wang, Jingjing; Zhang, Yuankui; Zhao, Yarong; Shi, Yanli (Frontiers in Microbiology, 2025)
Rotavirus A (RVA), a member of the Sedoreoviridae family, is significant intestinal pathogen that cause diarrhea in both piglets and humans. During of an outbreak that struck nursing piglets with diarrhea, a human-porcine reassortment rotavirus, named as RVA/Pig-wt/China/HB05/2023/G9P[23] (hereafter referred to as HB05), was identified. This specific strain was found to be prevalent in pig farms in several regions, including Hebei, Liaoning, Sichuan, Zhejiang and Henan, and caused significant economic losses from March to August 2023. To further explore the evolutionary diversity of HB05, a comprehensive analysis of all gene segments was conducted. The genome constellation was identified as G9-P[23]-I5-R1-C1-M1-A8-N1-T1-E1-H1. Nucleotide sequence identity and phylogenetic analyses indicated that the NSP3 gene of HB05 is most closely related to the corresponding genes of Human strains, with the highest homology at 95.45% identity. The other genes (VP1-VP4, VP6-VP7, NSP1-NSP2, NSP4-NSP5) exhibited the closest relationship to porcine strains, with the highest homology ranging from 94.79 to 98.89% similarity. Therefore, it is likely that HB05 originated from genetic reassortment between porcine and human rotaviruses. The pathogenicity study performed on 3-day-old piglets revealed that severe diarrhea manifested 8 h post-infection after oral inoculation with the PoRV HB05 strain at a dose of 2 × 10^5.5 TCID50/mL per piglet. To our knowledge, this marks the first report of a prevalent and highly virulent human-porcine reassortment G9P[23] rotavirus A (RVA) strain identified in mainland China. This finding provides valuable insights into the evolutionary traits of the G9P[23] strain and suggests a possible risk of cross-species transmission.